2010
DOI: 10.5034/inquiryjrnl_47.04.296
|View full text |Cite
|
Sign up to set email alerts
|

Coverage, Utilization, and Health Outcomes of the State Children's Health Insurance Program

Abstract: This paper uses data from the National Survey of America's Families (1997–2002) to explore the links between eligibility for the State Children's Health Insurance Program (SCHIP), health insurance coverage, medical care utilization, and health outcomes. We find that SCHIP significantly increased health insurance coverage rates for American children between 1997 and 2002, with most of the gains in coverage for older children. Higher coverage rates translated into increased utilization of the types of medical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…An analysis by Currie and Gruber (1996a) suggests that the first of these two effects dominates: Medicaid eligibility increases the probability of having a hospital stay by about 4 percentage points, which represents 24. Other studies using different data and different research designs also find that utilization increased for children who gained eligibility for public insurance because of CHIP relative to children who did not gain eligibility (Selden and Hudson 2006;Lurie 2009;Li and Baughman 2010;Choi, Sommers, and McWilliams 2011).…”
Section: Children Infants and Pregnant Womenmentioning
confidence: 99%
“…An analysis by Currie and Gruber (1996a) suggests that the first of these two effects dominates: Medicaid eligibility increases the probability of having a hospital stay by about 4 percentage points, which represents 24. Other studies using different data and different research designs also find that utilization increased for children who gained eligibility for public insurance because of CHIP relative to children who did not gain eligibility (Selden and Hudson 2006;Lurie 2009;Li and Baughman 2010;Choi, Sommers, and McWilliams 2011).…”
Section: Children Infants and Pregnant Womenmentioning
confidence: 99%
“…Consistent with our study findings, other investigators have found that doctor visits for nonemergency health care among older children (6 to 17 years of age) have increased since expanding children's health care coverage through CHIP. 2 Kenney's analysis of CHIP's effects across 10 states also found that enrolled children were more likely to have improved access to private physician offices as their usual source of care. 9 Our study builds on this prior work by using a different national data source over more years, including the pre-CHIP era, and dual investigation of the outpatient and ED settings.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the program, income-eligibility thresholds were increased for children in all age groups, with the most notable increases seen in adolescents. 2 Through streamlined enrollment and outreach efforts, the provision of coverage through CHIP along with Medicaid resulted in a decrease in uninsured rates among near-poor children. [3][4][5][6] Since the implementation of CHIP, several state-level analyses have found that newly enrolled children have improved access to a usual source of care and specialty care, as well as preventive care visits, and have also found higher parental satisfaction with the quality of health care services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Almost previous studies on the impact evaluation of child health insurance exclusively focus on children' medical care outcomes and child health as well, for examples Bailey et al (2016), Li and Baughman (2010), Zimmer (2011) for the U.S.A., Peng and Conley (2016) for China, or Wehby (2013) for South America. However, these studies disregarded other potential effects on other members within a family, importantly their parents.…”
Section: Introductionmentioning
confidence: 99%